APLIKASI MOBILE STUDENT ASSISTANT MAHASISWA ILMU KOMPUTER FMIPA UNIVERSITAS LAMPUNG BERBASIS ANDROID - Yusman, Machudor; Irawati, Anie Rose; ariska, bintang (Universitas Lampung, 2017)
Students are still often not on time in attending lectures, students also often forget to do the task and prepare for the exam. This has an impact on the achievement value obtained is not maximal. In this research, researchers built a mobile application on Android-based smartphone operating system as a reminder for students Computer Science Faculty of Mathematics and Natural Sciences University of Lampung. This application is made up of two parts Web-based for admin and Android-based for users, connected using Web Service. This application is made to support and maximize lecture activities. The workings of this application is as an alarm reminder to remind students of lecture, tasks, and exam schedules. The test result by using Black-Box equivalence partitioning shows that the application runs in accordance with the requirements.